Antimicrobial flavonoids isolated from Indian medicinal plant Scutellaria oblonga inhibit biofilms formed by common food pathogens. Issue 17 (1st September 2016) - Rajendran, Narendran; Subramaniam, Shankar; Christena, Lowrence Rene; Muthuraman, Meenakshi Sundaram; Subramanian, Nagarajan Sai; Pemiah, Brindha; Sivasubramanian, Aravind
Abstract: Scutellaria oblonga Benth., a hitherto phytochemically unexplored Indian medicinal folklore plant was extracted with acetone and subjected to chromatography to yield nine flavonoids, for the first time from this plant. Antimicrobial assays were performed against 11 foodborne pathogens, and three molecules (Techtochrysin, Negletein and Quercitin-3-glucoside) depicted significant activity. These molecules were assessed for their rate of antibacterial action using time–kill curves which depicted complete inhibition of most of the bacteria within 12–16 h. The significant biofilm-reducing capability exhibited by these three molecules formed a significant finding of the current study. In most of the experiments, a 90–95% reduction in biofilms was observed. Thus, flavonoids as natural molecules from S. oblonga could be further researched to be used as potent antimicrobial and antibiofilm agents. Abstract :